Acute Dermatotoxicity of Green-Synthesized Silver Nanoparticles (AgNPs) in Zebrafish Epidermis - Grace Emily Okuthe; Busiswa Siguba (Toxics)
Silver nanoparticles (AgNPs), lauded for their unique antibacterial and physicochemical attributes, are proliferating across industrial sectors, raising concerns about their environmental fate, in aquatic systems. While “green” synthesis offers a sustainable production route with reduced chemical byproducts, the safety of these AgNPs for aquatic fauna remains uncertain due to nanoparticle-specific effects. Conversely, mast cells play crucial roles in fish immunity, orchestrating innate and adaptive immune responses by releasing diverse mediators and recognizing danger signals. Goblet cells are vital for mucosal immunity and engaging in immune surveillance, regulation, and microbiota interactions. The interplay between these two cell types is critical for maintaining mucosal homeostasis, is central to defending against fish diseases and is highly responsive to environmental cues. This study investigates the acute dermatotoxicity of environmentally relevant AgNP concentrations (0, 0.031, 0.250, and 5.000 μg/L) on zebrafish epidermis. A 96 h assay revealed a biphasic response: initial mucin hypersecretion at lower AgNP levels, suggesting an early stress response, followed by a concentration-dependent collapse of mucosal integrity at higher exposures, with mucus degradation and alarm cell depletion. A rapid and generalized increase in epidermal mucus production was observed across all AgNP exposure groups within two hours of exposure. Further mechanistic insights into AgNP-induced toxicity were revealed by concentration-dependent alterations in goblet cell dynamics. Lower AgNP concentrations initially led to an increase in both goblet cell number and size. However, at the highest concentration, this trend reversed, with a significant decrease in goblet cell numbers and size evident between 48 and 96 h post-exposure. The simultaneous presence of neutral and acidic mucins indicates a dynamic epidermal response suggesting a primary physical barrier function, with acidic mucins specifically upregulated early on to enhance mucus viscosity, trap AgNPs, and inhibit pathogen invasion, a clear defense mechanism. The subsequent reduction in mucin-producing cells at higher concentrations signifies a critical breakdown of this protective strategy, leaving the epidermis highly vulnerable to damage and secondary infections. These findings highlight the vulnerability of fish epidermal defenses to AgNP contamination, which can potentially compromise osmoregulation and increase susceptibility to threats. Further mechanistic research is crucial to understand AgNP-induced epithelial damage to guide sustainable nanotechnology.